Manejo y uso eficiente del tamaño, uniformidad y distribución de la gota de pulverización en cultivo de soja (Glycine max L. Merrill) - Álvarez, Iván José M. (2016)
Currently, control of pests in soybean cultivation, is through land and air sprays. Faced with a high leaf density, used techniques that concentrate active ingredients in the upper leaves hurting the middle and basal leaves compromising the efficiency of control costs and impact on environment. This study evaluated the penetration, distribution and homogeneity of the appearance of drop in six models of hydraulic rotary nozzles and sprinklers sprayed determining that will fit the needs of culture control. The experiments were performed in a batch for the production, close to the town of Bandera (Santiago del Estero, Argentina). Treatments consisted of quality characterize droplet spectrum using water sensitive cards complemented by tracking tracer sodium fluorescein (C.I. 45350) with and without adjuvants, self-propelled agricultural machinery by spraying with 28 m working width, equipped with hollow cone nozzles HCX 6 (20 L.ha-1 5 bar), AD5/AN13 (30 L.ha-1 6 bar), AD5/N23 (40 L.ha-1 6 bar), TXV 12 (60 L.ha-1 3,8 bar), PPV 02 (100 L.ha-1 4 bar) and rotary sprinklers in aerial spraying (6 and 18 L.ha-1). The design was completely randomized in factorial scheme 5 (nozzles) x 2 (with and without adjuvant) and 4 repetitions, leaves were collected and washed with posterior tracer quantification by spectrophotometry. The results dictate that the amounts of applied marker with high flow increase the upper canopy decreasing basal and middle leaves, low flow increase show opposite results however are improved by the adjunct. Aerial spraying was higher than the earth, in the amounts of tracer distribution and quality of the droplet spectrum.